Uma prática educativa ambiental na construção de agenda 21 local - Santos, Ana Ferreira dos (2010)
This proposal is to search, investigate practical experience in environmental education for the construction of Local Agenda 21, in the municipality of Maxaranguape-RN, attended that brought together various subject and collective social actors of civil society organizations, among them, the Center for Education and Advice Herbert de Souza - CEAHS (NGOs who serves on the council since 1999), associations of farmers and farmers in areas of settlements, teachers / as, groups of women and young people, entrepreneurs, public power, the German partner entities IBAMA. INCRA, BNB in the project of Agenda 21. They are members and participants, constituents of the Permanent Forum of Agenda 21, the main actor privileged in the search. As an object of study to identify the limits and scope of this practice, with regard to aspects of awareness / participation and awaken to an awareness of critical social subjects in the collective social and environmental perspective. The study seeks to investigate if this experience has allowed the individual and collective social subjects, understand and act in their daily life, as the changes in attitudes postures, and expand their interests to participate in various public spaces this intention, is considered the educational activities made with the principles of environmental education in the construction of Agenda 21 that have contributed in raising awareness / participation of social actors of the Permanent Forum of Agenda 21. While reference methodology, the research focuses on theoretical design Freireana with relevance on the dimensions of dialogue, critical thinking and the human dimension comprising the act as educational practice of freedom, the prospect of human emancipation and social transformation of reality, and bring other thinkers as, Carvalho (2004), Trigueiro (2003), Days (2004), among others. The investigation of this practice points to the subject of education, which ECOCIENCIA to install the Agenda 21 and its effect on demand under municipal, German, providing a change of attitudes and postures and certainly, generating a new look and act in the world, broadening their interests and desires of inserting themselves, to participate in public spheres, particularly in establishing relations with dialogical criticality with the authorities and face the demands socio-environmental locations.